(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, a scientific study will be conducted on the life and political and historical activities of Muhammadwal Khan Darwazi. The work on ensuring the continuity of international policy, ensuring the independence and freedom of Afghanistan, and changing the attitude of the international community will undoubtedly further enrich the fate of the country, which has been under the rule of a large industrial state for many years. being the leader of large and powerful political and economic countries, a supporter of the bourgeois system, this state was one of the most important problems facing Muhammad Walihan Darwazi, and fought with his political leadership. After all, it was on this complex and important historical management that the whole fate and formalization of the true independence of the country that the world was waiting for depended.